Executive Committee Minutes 2021-04-29 - Academic Senate:::::::::
Approval of Agenda – item added: Credit Hour Policy. Approved. No report from the Chair. President Report. Provost Report. Vice President of Administration and Finance Report. Statewide Senator Report. Vice Chair Report. Vice President for Student Affairs Report. Associated Students Report. APARC Report. EPC Report. FSAC Report. From SAC: Discussion of Priority Registration policy. Selection and appointment and duties of department chairs policy approved for the Senate agenda. Senate reconsideration of endorsement of teaching of sensitive materials statement – Approved for Senate agenda. Credit Hour Policy approved as Information Item for Senate. Senate agenda approved.